Radial distribution of radiation in a CuBr vapor brightness amplifier used in laser monitors - Gubarev F. A. Fedor Aleksandrovich; Trigub M. V. Maksim Viktorovich; Klenovskii (Klenovsky) M. S. Miron Stanislavovich; Li Lin; Evtushenko G. S. Gennady Sergeevich (2016, 2016)
Title screen